Feasibility study of ‘Triple-Low’ technique for coronary artery computed tomography angiography (CCTA) - Shaochuan Wang; Zhengwen Sun; Yihong Zeng; Xinyu Xu; Yan Wang; Xueqin Liu; Yonggui Yang (Scientific Reports)
Abstract This study aims to explore the feasibility of applying the “Three-Low” technique (low injection rate, low iodine contrast volume, low radiation dose) in coronary CT angiography (CCTA). We prospectively collected data from 90 patients who underwent CCTA at our hospital between 2021 and 2024. The patients were randomly assigned to either the experimental group (n = 45) or the control group (n = 45). The experimental group parameters were as follows: injection rate of 3.5-4.0 ml/s, iodine contrast volume of 35–40 ml, tube voltage of 100 kVp, and tube current of 250 mA. The control group parameters were: injection rate of 4.5-5.0 ml/s, iodine contrast volume of 45–50 ml, tube voltage of 120 kVp, and tube current of 450 mA. Both groups received a high-concentration, non-ionic, water-soluble contrast agent (Iomeprol, 40 gl/100 ml). The heart rate of all patients was ≤ 70 bpm, and breath-hold scanning was performed after breathing training. The study compared the CT values of the left anterior descending artery, left circumflex artery, right coronary artery, and aorta, as well as background noise, signal-to-noise ratio (SNR), volumetric CT dose index, dose-length product, effective radiation dose, and total iodine dose between the two groups. In the control group, no cases of contrast extravasation occurred, while 6 cases of extravasation were observed in the experimental group (p = 0.026). There was no significant difference between the groups in terms of vascular image quality (mean vascular image quality score: experimental group 4.27 ± 0.62 vs. control group 4.24 ± 0.57, p > 0.05) or vascular motion artifact score (mean vascular motion artifact score: experimental group 4.20 ± 0.59 vs. control group 4.13 ± 0.55, p > 0.05). However, significant differences were found between the experimental and control groups in the CT values of the left anterior descending artery (experimental group: 571.31 ± 49.66 HU vs. control group: 449.20 ± 36.80 HU, p < 0.05), left circumflex artery (experimental group: 570.41 ± 49.98 HU vs. control group: 450.95 ± 39.27 HU, p < 0.05), right coronary artery (experimental group: 584.52 ± 53.70 HU vs. control group: 452.66 ± 40.67 HU, p < 0.05), aorta (experimental group: 624.91 ± 48.99 HU vs. control group: 465.36 ± 34.37 HU, p < 0.05), background noise (experimental group: 24.76 ± 1.97 vs. control group: 19.09 ± 1.69, p < 0.05), SNR (experimental group: 25.30 ± 1.81 vs. control group: 24.47 ± 1.75, p < 0.05), volumetric CT dose index (experimental group: 22.97 ± 1.47 mGy vs. control group: 50.53 ± 4.89 mGy, p < 0.05), dose-length product (experimental group: 363.68 ± 21.45 mGy·cm vs. control group: 782.41 ± 58.20 mGy·cm, p < 0.05), and effective radiation dose (experimental group: 5.09 ± 0.30 mSv vs. control group: 10.95 ± 0.81 mSv, p < 0.05).The results of the Fisher test indicated that the extravasation rate was significantly higher in the high injection rate group compared to the low injection rate group (P = 0.024). The “Three-Low” technique in CCTA imaging effectively reduces the incidence of contrast extravasation caused by high injection rates and decreases the radiation dose, making it a highly feasible option for clinical application and worthy of broader adoption.